Time trends in patients managed simultaneously in multiple hospital outpatient specialty clinics for chronic diseases: A register-based cross-sectional study. (25th February 2019) - Wolff, Donna Lykke; Von Plessen, Christian; Waldorff, Frans Boch; Sørensen, Thomas Lund; Bogh, Søren Bie; Rubin, Katrine Hass; Mogensen, Christian Backer
Background: The increasing prevalence of patients with multimorbidity in the general population affects the health-care system. There is a lack of knowledge of the proportion of patients attending multiple hospital outpatient specialty clinics simultaneously. Objective: This study describes the development in the proportion of patients managed simultaneously in multiple hospital outpatient specialty clinics. Design: We obtained three cross-sectional samples from all of the hospitals in Denmark. The data set consists of adults (age 18+) in long-term outpatient care on January 1 in 2004, 2009, and 2014 with one or more of 50 consensus-selected chronic diseases. Descriptive statistics were used to examine and compare the proportion of patients treated simultaneously in multiple outpatient specialty clinics. We also investigated the most common combinations of outpatient specialty clinics. Results: In 2004, 176, 786 patients with chronic diseases were registered as receiving outpatient care in Denmark. This figure increased to 246, 542 patients in 2009 and 341, 015 in 2014. The proportion of patients managed simultaneously in multiple outpatient specialty clinics was 4.0% in 2004, 5.5% in 2009, and 7.7% in 2014. The most common specialty clinic combination was endocrinology and cardiology, accounting for 12.1% in 2004, 11.5% in 2009, and 9.6% in 2014. Conclusions: The proportion of patients in multiple clinics nearly doubled over a 10-year period. While there were some common specialty clinic combinations in which patients were treated most often, there was also considerable variation. Further studies are needed to identify generic and disease-specific initiatives.